Networking in Japanese Factory Automation. - Kishimoto, Koichi (Taylor & Francis, 2010)
In Japan information technology has been a vital part of manufacturing for decades. A central factory computer provides a production plan and shop minicomputers and microcomputers in the factory run machines that manufacture products. It has become necessary to connect computers installed at different locations to enable information exchange between different sections. This volume discusses the ring-type LAN; the TOSLINE-8000 high-speed optical data highway for high-speed real-time control systems; the TOSLINE-2000E, a compact, low-cost independent local area network; the status of MAP, a comm.